VALUASI EKONOMI OBJEK WISATA KAWASAN PANTAI BARON GUNUNG KIDUL APLIKASI TRAVEL COST METHOD - Hendro Wibowo (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2021)
The Baron Beach Area is one of the favorite beach attractions with the highest number of visitors in Gunung Kidul Regency. However, the presence of coastal abrasion and decreasing environmental quality needs to be a concern for the management. Understanding of the economic value and visitor characteristics is important for management considerations in a more optimal and effective coastal management. Economic valuation is an important instrument for estimating the monetary value of benefits and changes in benefits obtained by humans from natural resources, such as beaches. This study aims to estimate the economic value of the Baron Beach Area using the Individual Travel Cost Method. The variables used are travel cost (TC), expenditure (EXPEND), age (AGE), education level (EDU), other tourist object substitution dummy (DS), and environmental quality dummy (DENVR). This count data study used the negative binomial regression method. The results showed consumer surplus per person per visit was IDR 282,531.00 and total economic value of the Baron Beach Area was IDR 560,182,653,564.00 per year.